A STUDY ON MANAGEMENT PRACTICES IN PET BIRDS IN THRISSUR DISTRICT - M.P Sreeshma; N Geetha; P Reeja George; Manju Sasidharan; Sabin George; K.S Anil; C Sunanda (Journal of Veterinary and Animal Sciences, 2018)
A detailed study was undertaken in the management practices of pet birds in relation to breeding, health care, welfare and marketing in ThrissurDistrict of Kerala. A detailed questionnaire was prepared and data collected from 35 aviculturists to operationalize the study. In this study, identification of sex in birds is a major problem faced by bird owners. Most of the bird owners identified sex by their own experience . Deoxyribo nucleic acid (DNA) sexing is the scientific method of sex identification. Almost all owners used birds for breeding purpose throughout the year. Age at which the birds were used for breeding varied with species. Natural method of incubation was followed by all the owners. Mortality was reported more in rainy season. Most pet birds spend full time in the cages. De-worming and vaccination were the only health management practices followed. The owners gave timely medications to common diseases of the birds. The birds were very friendly and liking towards their owners. All birds in this survey were comfortable with their managemental practices. None of the owners had given any training to the birds.